Fiscal Sustainability in African HIPC Countries : A Policy Dilemma? - Fedelino, Annalisa (IMF Working Papers; Working Paper ;, 2003)
This paper looks at the link between fiscal policy and debt sustainability in a number of African countries participating in the Heavily Indebted Poor Countries (HIPC) Initiative. The paper finds that, on the basis of current fiscal policies, debt levels will remain unsustainable even after these countries graduate from the HIPC Initiative. This finding has important policy implications. By the very requirements of the HIPC Initiative, these countries are expected to increase significantly their poverty-reducing expenditure-possibly resulting in weaker fiscal primary balances and worsening debt sustainability outlook. As offsetting fiscal tightening may not be viable, ensuring debt sustainability may thus require increased availability of (nondebt-creating) grants. Otherwise, debt sustainability in HIPC countries may prove elusive in the long term.